Congenital Hypothalamic "Hamartoblastoma" Versus "Hamartoma": Suggestions for Neuropathologic Terminology Emanating From a Mid-gestational Autopsy Case of Pallister-Hall Syndrome. (May 2018) - Dunham, C; McFadden, D; Dahlgren, L; Butler, B; Hamilton, S; McKinnon, M
Pallister-Hall syndrome (PHS) is a rare malformative disorder that is due to truncating functional repressor mutations in GLI3 . Since the seminal publication in 1980, hypothalamic tumors have been recognized to be a cardinal feature of PHS. In their original description of the neuropathologic features of PHS, Clarren et al. coined the term "hamartoblastoma" to characterize what they deemed to be a dual malformative and neoplastic mass of the hypothalamus. In subsequent published cases/series of PHS, the term "hamartoma" was often substituted for hamartoblastoma given what appeared to be a benign natural history of this lesion. Additional confusion in the literature has ensued since most hypothalamic hamartomas (HH) encountered on the clinical neuropathology service are "isolated" in nature (ie, no other congenital malformations) and present in a very different and stereotypical fashion with gelastic seizures and/or precocious puberty. While genomic investigations of isolated HH have begun to uncover a mutational profile of these cases, GLI3 mutations have only been recognized in a small subset of isolated HH. Herein, we describe the autopsy findings from a 21-week gestational age fetus with features of PHS. Moreover, we provide a detailed description of the hypothalamic tumor affecting this fetus and propose a novel subclassification of HH, distinguishing syndromic from isolated forms based upon the presence or absence of neocortical-like areas.